2021
DOI: 10.1002/chem.202004831
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbapenems Containing Peptidoglycan Mimetics and Inhibition of the Cross‐Linking Activity of a Transpeptidase of l,d Specificity

Abstract: The carbapenem class of β‐lactams has been optimized against Gram‐negative bacteria producing extended‐spectrum β‐lactamases by introducing substituents at position C2. Carbapenems are currently investigated for the treatment of tuberculosis as these drugs are potent covalent inhibitors of l,d‐transpeptidases involved in mycobacterial cell wall assembly. The optimization of carbapenems for inactivation of these unusual targets is sought herein by exploiting the nucleophilicity of the C8 hydroxyl group to intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Unfortunately, the success of such "peptidoglycan mimetics" has been mixed. [108][109][110][111][112] For instance, the introduction of two extended arms to the cephalosporin core with peptide motifs that mimic the acyl donor and the acyl acceptor, respectively, improved the compound's specificity: it inhibited the TP activity of E. coli PBP1b selectively in vitro but showed no interaction or inhibition against E. coli PBP5 (a carboxypeptidase, CP). [111] In another work, Josephine et al demonstrated that the addition of side chain extensions onto β-lactams unexpectedly improved the inhibition of LMW PBPs, but not the bPBPs in vitro.…”
Section: Peptidoglycan Mimetics Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the success of such "peptidoglycan mimetics" has been mixed. [108][109][110][111][112] For instance, the introduction of two extended arms to the cephalosporin core with peptide motifs that mimic the acyl donor and the acyl acceptor, respectively, improved the compound's specificity: it inhibited the TP activity of E. coli PBP1b selectively in vitro but showed no interaction or inhibition against E. coli PBP5 (a carboxypeptidase, CP). [111] In another work, Josephine et al demonstrated that the addition of side chain extensions onto β-lactams unexpectedly improved the inhibition of LMW PBPs, but not the bPBPs in vitro.…”
Section: Peptidoglycan Mimetics Inhibitorsmentioning
confidence: 99%
“…Given that β‐lactams mimic the d ‐Ala (IV) ‐ d ‐Ala (V) terminus of the acyl acceptor in the transpeptidation reaction, efforts have been made to rationally modify the β‐lactam core with side chain extensions that resemble the canonical stem peptide or branch peptide. Unfortunately, the success of such “peptidoglycan mimetics” has been mixed [108–112] . For instance, the introduction of two extended arms to the cephalosporin core with peptide motifs that mimic the acyl donor and the acyl acceptor, respectively, improved the compound's specificity: it inhibited the TP activity of E. coli PBP1b selectively in vitro but showed no interaction or inhibition against E. coli PBP5 (a carboxypeptidase, CP) [111] .…”
Section: Transpeptidases (Tps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbapenems have been heavily explored with multiple drugs on the market, while penems are only represented commercially by faropenem. Meropenem, a member of the carbapenem subclass, in combination with clavulanate, a β-lactamase inhibitor, has shown unmistakable bactericidal activity in the sputum of TB patients and has been used effectively in the clinic for treating MDR TB infections. These results have spurred interest in developing new carbapenems against Mtb . , The recent development of atypical carbapenems has shown promising progress against Mtb and Mab . Additionally, faropenem and the newly developed penem T405 have displayed potent activity against Mtb and Mab . , While carbapenems have been the main focus in β-lactam development against TB, penems remain relatively unexplored.…”
mentioning
confidence: 99%
“…12−15 These results have spurred interest in developing new carbapenems against Mtb. 16,17 The recent development of atypical carbapenems has shown promising progress against Mtb and Mab. 18 activity against Mtb and Mab.…”
mentioning
confidence: 99%